Awareness of health sciences students about colorectal cancer risk factors - Üstündağ, Hülya; Zengin, Neriman; Andsoy, Işıl Işık; GÜL, ASİYE (My University, 2019)
Objective This descriptive study was conducted in order to determine the risk factors, symptoms and awareness of health sciences students with regards to colorectal cancer (CRC). Methods This study included 1,028 health science students from two different universities. Data for this study were collected via a questionnaire form that included questions about CRC risk factors, protective approaches and symptoms. Frequencies, percentages and averages of the data were assessed with Kruskal-Wallis and Mann-Whitney U tests. Results The most frequent risk factors of the students (mean age: 21.25 years) were smoking (90.5%), excessive alcohol consumption (87.4%), family history of cancer (84.2%) and obesity (82.6%), while the most common protective approaches were smoking cessation, avoiding alcohol, regular physical activity and a low-fat diet. There was a significant difference in the CRC awareness of students in terms of gender, the department and grade level at which they were studying, and having a family history of cancer. Conclusion Results of this study revealed that students had a sufficient awareness about risk factors and what they could do to diminish their risk, but their knowledge about CRC symptoms was less than expected. We believe that health sciences students should be given more education on CRC symptoms.
Keywords: Awareness of Risk Factors; Bowel Cancer; Colorectal Cancer; Health Sciences Students; Risk Faktörlerinin Farkındalığı; Kolon Kanseri; Kolorektal Kanser; Sağlık Bilimleri Öğrencileri